Anti-Diabetic Properties of Bitter Gourd - Sharma, Shweta; Katoch, Viveka (International Journal of Economic Plants, 2020)
Bitter gourd (Momordica charantia L.) is a fruit that traditionally believe to have benefits on health. It is a widely used traditional remedy for the treatment of diabetes. Bitter gourd is suggested for hyperglycemia treatment due to its ability to reduce glucose levels in the body. Some of the bioactive compounds present in it possess anti diabetic effects. It contains phytochemicals with anti-diabetic properties such as charantin, p-insulin and vicine. Hypoglycemic effects of bitter gourd have been shown in clinical studies. This review will focus on the hyperglycemic properties of bitter gourd.